Obraz współczesnego społeczeństwa w utworach muzycznych Doroty Masłowskiej – Mister D. - Wrzochul-Stawinoga, Justyna (Kultura-Społeczeństwo-Edukacja, 2018)
Changes resulting from the development of the Internet have a significant impact on the shape of popular culture. Music, particularly the message that it conveys, constitutes an important element of culture. Music, which is a part of a wider cultural context, has a significant influence on the shaping of the world view of contemporary people and serves as an important element of its description. According to Jacek Bernasiewicz, music often becomes the building block of the young generation. “It is primarily about music, and particularly its content, that always served as a generational bond and carried ideology – rock music for flower children, punk rock for neglected children, rap music for hip hoppers…” (Bernasiewicz, 2009: 4). Music always carries a message and combined with a music video, it becomes a story. This paper and deliberations contained herein are devoted to the works of Mr D, also known as Dorota Masłowska, which is a mirage – on the one hand of pop culture, entertainment and fun, and on the other, a depiction of the contemporary Polish society, in which the Generation Y plays a major role. The aim of the paper is to show how the Internet, being a place where narratives about the world play out, using the convergence of media, contributes to the construction of a certain reality, the elements of which, emphasised by Dorota Masłowska and elevated above the everyday life of the global teenager “Made in Poland,” make up the determinants of contemporary youth culture. Music videos by Mr D. and the content of songs from the album Społeczeństwo jest niemiłe will serve as the subject of this analysis. The narrative appearing in these songs will be examined, and the broader context of the meanings contained in the songs in relation to the entirety of popular culture and the way of functioning of society in it will be pointed out. Dorota Masłowska’s songs are not narratives of the author herself, but of protagonists presented in her music videos: the girl presented in the music video undergoes a kind of metamorphosis, and the viewer looks at the world through the eyes of her imagination. The protagonists in her music videos and songs are representatives of certain social groups with specific, clear characteristics that allow them to be individually identified. I assume that lyrics of songs listened to and music videos watched by youth and young adults are among the most important ways of learning and participating in culture by giving meaning to oneself, one’s life and the world. A musical work that is an “immature form” of culture, making use of the wide range of possibilities available to it for conveying messages, full of symbols and metaphors, demands its recipients to read and discover the meaning.